The art of coaching vs. the science of movement: Integrating experiential knowledge and scientific evidence into coaching practices - Waters, A. (Victoria University, 2020)
The overall aim of this research was to examine the factors that influence the coach-biomechanist relationship in the elite sprinting context and gain an understanding of the factors that impede and enhance performance environments and relationships. It is thought that the transfer of sport science research into coaching practice is not as efficient as it should be, as it has been established that coaches are not using sport science as a source of knowledge. Subsequently, this insufficient transfer of knowledge could be limiting potential improvements in athlete performance. Technique analysis is a common area of expertise for both sprint coaches and biomechanists in high-performance sport and was therefore the ideal context to explore the coach-biomechanist relationship in detail. The first phase of research examined the coach and biomechanists` understandings of optimal sprint running technique and determined the relationships between the experiential knowledge of the two groups. Findings showed elements that are crucial to optimal sprinting technique, such as the position of the contact foot and extension of the leg during stance. Differences in knowledge between the two groups were complimentary. For example, the biomechanists` focus on the transition from swing into stance phases and the coaches` interest in upper body movement. Moreover, the communication of these knowledge differences was potentially problematic. The second phase of this research determined if the knowledge differences found in the first phase influenced the visual search patterns of coaches and biomechanists. This difference was not observed, with visual search behaviour not reflecting the differences in knowledge seen in phase one. The third phase aimed to establish the context in which coaches and biomechanists interact to improve performance. This phase supported previous phases` results in that communication styles and knowledge differences were impeding factors and added lack of role clarity to this list. The fourth and final phase investigated the interactions and exchange of information that occurs during the technique assessment process. Results showed that the process is a coach-led partnership where rapport building, and equal sharing of knowledge are emphasised. In summary, this research contributes to the understanding of the coach-sport science relationship by providing practical evidence for numerous concepts in a novel and more specialized population. It increases our understanding of coach technical knowledge and visual perceptual behaviour as well as uniquely incorporating the sport biomechanists` knowledge and perspective into these investigations. The multi-layered approach used allowed the knowledge, behaviours and interactions that comprise qualitative analysis of technique to be investigated. This has greatly improved our understanding of the coach- biomechanist relationship and the factors that impede and enhance it.